(untitled) (Swiss Medical Weekly, 2012)
Allergy and asthma are complex diseases influenced by many genes and molecular mechanisms. Recently a number of genome-wide association studies (GWAS) have investigated asthma- and allergy-related phenotypes. Results suggest the existence of sub phenotypes of asthma and document a need to better define the disease. Genetics may also help to identify groups of patients susceptible for specific forms of treatment and those at risk for adverse effects of therapy. Thus, genetics may represent a key tool to achieve individualised medicine in asthma and allergy in the future.